2021
DOI: 10.1108/maj-08-2020-2808
|View full text |Cite
|
Sign up to set email alerts
|

Economic policy uncertainty and audit effort: evidence from audit hours

Abstract: Purpose This paper aims to examine the association between economic policy uncertainty (EPU) and audit effort by focusing on audit hours. This paper also explores whether significant political uncertainty might amplify the positive association between EPU and audit effort by focusing on Korea. Design/methodology/approach This study uses 21,543 Korean firm-year observations from 2005 to 2018 in an audit hour determinant model, as well as EPU following Baker et al. (2016) and audit hour to proxy audit effort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Another strand of research has explored the external economic or legal factors on audit quality and audit fees. Yun and Chun (2021) show that auditors work more audit hours in response to economic policy uncertainty. Gong et al (2022) find a negative effect of COVID-19 on audit quality.…”
Section: Introductionmentioning
confidence: 93%
“…Another strand of research has explored the external economic or legal factors on audit quality and audit fees. Yun and Chun (2021) show that auditors work more audit hours in response to economic policy uncertainty. Gong et al (2022) find a negative effect of COVID-19 on audit quality.…”
Section: Introductionmentioning
confidence: 93%
“…Existing literatures suggest that economic policy uncertainty exposes firms to greater risk, raises the cost of corporate finance and reduces the availability of credit resources [ 44 , 45 ]. Economic policy uncertainty increases information asymmetry between auditors and clients, which in turn increases audit risk and audit fees [ 46 ]. International network members usually have a higher reputation and therefore suffer more serious losses in the event of an audit failure.…”
Section: Further Analysismentioning
confidence: 99%
“…It is found that firms with internal control deficiencies tend to have lower-quality financial reports (Foster et al, 2007) and are more likely to have major misstatements or irregularities and engage in earnings management (Kinney, 2007;Lenard et al, 2016). To deal with the earnings manipulation, auditors work more audit hours to reduce firms' audit risk to an acceptable level (Yun and Chun, 2021). Therefore, when a firm violates environmental regulations, or has been punished for environmental violations, auditors are more sensitive to the increased risks of firms with internal control defects than to those of firms without internal control defects.…”
Section: Environmental Violations In Chinamentioning
confidence: 99%